Neonatal Survival Co-efficient of Very Low Birthweight Infant - Rajin Arora; Wanlika Kaeosuriya; Aintila Jongpoo (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objective: The aim of this study was to determine the survival co-efficient of very low birthweight (VLBW) infant (weighing < 1500 grams) at the age of 28 days and examine the survival ratios of infant at different birthweights. Materials and Methods: This retrospective cohort study included all live-born VLBW infants who delivered at Lampang Regional Hospital from January 1, 2005 - December 31, 2009. The maternal and neonatal medical records were reviewed. Data were analyzed using descriptive and inferential statistics.Results: There were 223 VLBW live-born infants during this period (11.7/ 1,000 live births). Mean (SD) of gestational age was 28.7 (3.4) weeks. Most of them had vaginal delivery. The mean (SD) birthweight was 1,124.8 (236.8) grams. The most common neonatal complication in this study was respiratory distress syndromes. Survival ratios at 28 days of VLBW infants stratified by 100 grams birthweight were ranging from 0-94.9%. Regression analysis showed survival co-efficient (OR) at 1.64 (95% CI 1.40-1.92). Conclusions: The incidence of VLBW infants and survival ratios at Lampang Regional Hospital were comparable to the other hospitals in Thailand. The survival co-efficient was 1.64 meant that a VLBW infant had 64% increased chance of survival for every 100 grams gained. The figure of survival co-efficient could very much help obstetric personnel in counseling a pregnant woman about the prognosis of her unborn child.